Andexanet Alfa: First Global Approval - Heo, Young-A (Drugs (New York, N.Y.), 2018)
Intravenous andexanet alfa [coagulation factor Xa (recombinant), inactivated-zhzo; Andexxa ® ] is a first-in-class recombinant modified factor Xa protein that has been developed by Portola Pharmaceuticals as a universal antidote to reverse anticoagulant effects of direct or indirect factor Xa inhibitors. In May 2018, andexanet alfa received its first global approval in the USA for use in patients treated with rivaroxaban and apixaban, when reversal of anticoagulant effects is required in life-threatening or uncontrolled bleeding. Intravenous andexanet alfa is under regulatory review in the EU and is undergoing clinical development in Japan. This article summarizes the milestones in the development of andexanet alfa leading to this first global approval for reversing anticoagulation of rivaroxaban and apixaban in adults.